Identify Students’ Misconceptions on Electrolysis using Two-Tier Diagnostic Test - Esrida Hutahaean; Pardiana Pardiana; Yanti Hadiyati (Journal of Research in Environmental and Science Education, 2024)
In the literature, lack of conceptual understanding makes it difficult for students to relate chemistry to their learning experience, leading to misconceptions. Misconceptions are defined as phenomena where students have concepts that differ from scientific concepts. Misconceptions will affect how students construct scientific knowledge in the next learning material. Therefore, the study of this misconception is an important concern in the field of education. The purpose of this study was to identify students’ misconceptions on electrolysis material. The instrument used in the study was a two-tier diagnostic test consisting of 10 questions at the first level and supporting reasons at the second level. The questions contained in this instrument are taken from previous research. This study used a qualitative descriptive approach involving 55 students from class XII Analytical Chemistry in one of the vocational high schools in Cilegon City. The results showed that out of a total of 55 students, there were students who understood the concept as much as 34%, students who experienced misconceptions as much as 30.73%, students who understood partially as much as 9.82% and students who did not understand the concept as much as 25.45%.